Evaluation of sintered bauxite proppant for binary enhanced geothermal systems - KC, Bijay; Ghazanfari, Ehsan; McLennan, John; Frash, Luke P.; Meng, Meng (Geomechanics and geophysics for geo-energy and geo-resources., 2024)
Solid granular proppant particles are widely used in oil and gas development to sustain permeability through fractures after hydraulic stimulation. Similar proppants are of interest for geothermal applications where the goal of sustaining permeability is the same, but the harsh geothermal environment risks rapid proppant degradation that will reduce fracture permeability. Here, we present proppant conductivity experiments using saw cut granite, tensile fractured granite, and aluminum control specimens packed with sintered bauxite ceramic proppants at concentrations of 0.0, 0.1, and 1.0 kg/m 2 . Simulated geothermal conditions included temperatures up to 130 °C and normal closure stresses up to 60 MPa. Compared to unpropped specimens, peak fracture conductivity enhancement was up to 6 orders of magnitude. At simulated geothermal conditions, proppants were able to sustain fracture conductivity over 60 h, but chemical dissolution and decreasing permeability over time were evident. Irreversible conductivity reductions with crushing and embedment of proppants during loading stages were also observed. Overall, sintered bauxite proppant remains a promising option for low-temperature binary-cycle enhanced geothermal systems. Article highlights Sintered bauxite proppant holds promise to enhance and sustain fracture conductivity under low-temperature EGS conditions. Proppant crushing and embedment lead to irreversible conductivity decline. Mineral dissolution from proppant and rock fracture will diminish the benefit of proppant over time.